IMPLEMENTATION OF THE PRINCIPLE OF RESTORATIVE JUSTICE IN THE CRIMINAL CASE SETTLEMENT PROCESS AT THE DENPASAR DISTRICT COURT - Wiratny, Ni Ketut; Sihotang , Erikson; Prihanta, Kadek Hendhy (Antis-Publisher, 2026)
Objective: To analyze the legal arrangements related to the application of restorative justice in the settlement of criminal cases at the Denpasar District Court. Method: The study uses a legal analysis approach, referencing Supreme Court Regulation Number 1 of 2024 concerning Guidelines for Prosecuting Criminal Cases Based on Restorative Justice (PERMA RJ), and examining a specific case decision (No. 1226/Pid.Sus/2024/PN Dps) to assess the application of restorative justice. Results: The implementation of restorative justice is seen through the involvement of victims, their families, defendants, and other related parties, with the aim of recovery instead of mere retaliation, as illustrated in the court decision. Novelty: The interpretation and application of restorative justice as defined in PERMA No. 1 of 2024 in criminal case settlements, especially in the Denpasar District Court, highlighting its goal of restorative rather than punitive outcomes.